HUBUNGAN KELEKATAN AMAN (SECURE ATTACHMENT) DENGAN RESILIENSI ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Widyia Asmariza; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the secure attachment that is resilient in children. Every child has a different level of resilience in dealing with a problem in his life, where children who have resilience who in themselves tend to be able to overcome the problems faced. Mother is a figure that a child has as a sticky figure, a child who has attachment tends to be strong in dealing with problems. This study aims to determine the relationship between secure attachment and resilience in children aged 5-6 years in TK Negeri Pembina 3, Marpoyan Damai District, Pekanbaru City. This research is a quantitative study with the type of correlation research. The population in this study was 122 children, as many as 55 children were sampled using the Taro Yamame formula. Data collection techniques used are observation. Data analysis techniques using Person Product Moment correlation techniques. It can be seen from the overall indicators of secure attachment in the good category with a percentage of 75.87% while in the resilience indicator in the good category with a percentage of 72.16%. Based on the results of hypothesis testing known from the value of the correlation coefficient of rxy = 0.282 and the significance level of 0.037 <0.05. Thus the level of secure attachment with Resilience is included in the strong category with the resulting coefficient of determination of 80%, that means that secure attachment has an effect of 80% on resilience.Key Words : Secure Attachment, Resilience.